Prisoners of Conscience Cases in Indonesia: The Rights of Fair Trial Perspective - Prawira, M. Rizki Yudha (Faculty of Law, Kadiri Islamic University (UNISKA) Kediri, 2024)
This study examines cases of prisoners of conscience (PoC) in Indonesia through the lens of the right to a fair trial. The patterns observed in these PoC cases include arbitrary arrest, imprisonment, torture, exile, and even enforced disappearance. Various examples illustrate these issues. According to data gathered by Amnesty International Indonesia, there are numerous instances related to PoC. Between August 2019 and April 2024, there were 128 prisoners of conscience (PoC) related to 82 cases in Indonesia. The same source indicates that many of these prisoners were incarcerated solely for their peaceful expressions. They have been charged under various laws, including the Information and Electronic Transactions Law, as well as laws concerning criminal blasphemy, treason, and pornography. This research uses normative juridical methods, specifically focusing on library legal research to examine secondary data and relevant legal materials. The approach adopted in this study is a statutory approach, which entails referencing legal issues or problems specifically pertaining to cases involving prisoners of conscience. This study also examines cases of PoC in Indonesia from the perspective of the right to a fair trial. It highlights the numerous violations of fair trial rights evident in the patterns of arrests leading to imprisonment in these cases.